2005
DOI: 10.1161/01.str.0000165920.67784.58
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA Reductase Inhibitors Improve Acute Ischemic Stroke Outcome

Abstract: Background and Purpose-Statins reduce the risk of stroke recurrence, but the benefits of statins in improving outcome of acute stroke patients have not been well explored. Methods-We assessed potential effects of statins initiated before or within 4 weeks of stroke on 90-day outcome.Favorable outcomes were National Institutes of Health Stroke Scale (NIHSS) score Յ2 at 12 weeks and modified Rankin Scale (mRS) Յ2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 7 publications
(2 reference statements)
7
68
0
4
Order By: Relevance
“…Although some trials have failed to find lipid lowering effects of other policosanol tablets [27][28][29], the cholesterollowering effects here seen are consistent with previous experimental [30][31][32][33][34] and clinical [35][36][37][38] data of policosanol. Since statins may improve outcomes in acute ischemic stroke [39,40], these effects of poli + AS treatment could have contributed to the neurological recovery of study patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although some trials have failed to find lipid lowering effects of other policosanol tablets [27][28][29], the cholesterollowering effects here seen are consistent with previous experimental [30][31][32][33][34] and clinical [35][36][37][38] data of policosanol. Since statins may improve outcomes in acute ischemic stroke [39,40], these effects of poli + AS treatment could have contributed to the neurological recovery of study patients.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Treatment of patients within 4 weeks after acute ischemic stroke with statins significantly increased favorable outcome at 12 weeks. 51 In addition, the efficacy, safety, and tolerability of statins have been confirmed in randomized, controlled, multicenter trials involving large numbers of patients aged Ն65 years. 52 Elderly patients taking lipid-lowering agents, such as statins, at the time of an ischemic stroke have lower poststroke mortality and a lower risk of worsening during hospitalization.…”
Section: Pharmacological Treatment Of Stroke Statinsmentioning
confidence: 95%
“…Additional studies shown that, besides the lipid-lower effect, at the same time lovastatin could stabilize the atherosclerotic plaque and have beneficial effects on cerebral circulation and brain parenchyma during ischemic stroke and reperfusion [34]. We measured the plaque thickness and volume of patients in three groups and found that lovastatin could significantly decreased plaque thickness and volume.…”
Section: Discussionmentioning
confidence: 91%